A Global Paleosecular Variation Database for the Paleogene: Stationary Secular Variation Behavior Since the Triassic? - Y. A. Engbers; D. Thallner; R. K. Bono; C. J. Sprain; M. J. Murray; K. Bristol; B. Handford; T. Torsvik; A. J. Biggin (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Paleosecular variation analysis is a primary tool for characterizing ancient geomagnetic behavior and its evolution through time. This study presents a new high‐quality directional data set, paleosecular variation of the Paleogene (PSVP), with and without correction for serial correlation, compiled from 1,667 sites from 45 different localities from the Paleogene and late Cretaceous (84–23 Ma). The data set is used to study the variability, structure, and latitude dependence of the geomagnetic field during that period by varying selection criteria and PSV models. Modeled values for the equatorial virtual geomagnetic pole (VGP) dispersion have over‐lapping uncertainty intervals within their uncertainty bounds between 8.3° and 18.6° for the past 250 Ma. We investigate the suitability of two descriptive models of PSV, Model G‐style quadratic fits and covariant Giant Gaussian Process models, and find that both styles of model fail to satisfactorily reproduce the latitude dependent morphology of PSV, but suggest that estimates of the equatorial VGP dispersion may still robustly characterize aspects of Earth's long‐term field morphology. During this time where the PSV behavior has not changed substantially, the reversal frequency has varied widely. The lack of a clear relationship between PSV behavior and reversal frequency is not trivially explained in the context of published findings regarding numerical geodynamo simulations.